Axitinib Reverses Resistance to Anti-Programmed Cell Death-1 Therapy in a Patient With Renal Cell Carcinoma - Yang, Yonghao; Huang, Hao; Li, Tiepeng; Gao, Quanli; Song, Yongping; Wang, Zibing (Frontiers in Immunology, 2021)
Owing to broad and notable clinical anti-tumor activity, anti-programmed cell death-1 (PD-1)/anti-programmed cell death-ligand 1 (PD-L1) antibodies have been indicated for almost all types of cancer, and form a part of the current standard of care. However, a large proportion of patients do not respond to anti-PD-1/PD-L1 therapy (primary resistance), and responders often develop progressive disease (acquired resistance). The mechanisms of resistance are complex and largely unknown; therefore, overcoming resistance remains clinically challenging, and data on reversing anti-PD-1 resistance are scarce. Herein, we report the case of a 58-year-old woman with renal cell carcinoma associated with Xp11.2 translocation/transcription factor E3 gene fusion, who had already showed resistance to both anti-PD-1 monotherapy and standard-dose axitinib. However, she finally achieved a partial response with a continuous combination therapy comprising low-dose axitinib and anti-PD-1. We speculate that axitinib played a key role in reversing the primary resistance to anti-PD-1 therapy. Interestingly, we observed that the number of peripheral regulatory T cells increased after the standard-dose axitinib therapy, with accompanied tumor enlargement; however, after the dose was reduced, the number of regulatory T cells decreased gradually, and the tumor regressed. We also reviewed relevant literature, which supported the fact that low-dose axitinib might be more beneficial than standard-dose axitinib in assisting immunotherapy. Given that this is a single-case report, the immunomodulatory effect of axitinib requires further investigation.